Lost in a Thyroid Storm – Psychosis as a First Presentation of Grave’s Disease - Eneida Karriqi; Emma Padfield (BJPsych Open, 2025)
Aims: Thyrotoxicosis is caused by an overactive thyroid gland, leading to excessive production and release of thyroid hormones into the bloodstream. The most common cause is Grave’s disease. Presentation of Grave’s disease with neurological and psychiatric symptoms as first line is rare; however it can lead to mis-diagnosis of a primary psychiatric condition, especially in younger patients. This report illustrates the case of a 24-year-old female presenting with psychotic symptoms on a background of undiagnosed Grave’s disease.